Use of Mobile Phone Applications in Cardiopulmonary Resuscitation: Scoping Review - Dian Herdiana; Tuti Herawati (Journal of Nursing Care, 2023)
Cardiopulmonary resuscitation has to start as early as possible to increase the survival rate of life. The mobile phone application is one of the method that can be used to deliver victims immediately to seek help and provide guidance in these situation. This study aims to search the literature and analyze articles discussing the use of mobile phones in Cardiopulmonary resuscitation. The design used was a scooping literature review with PRISMA adaptation. Articles were searched using databases: ProQuest, ScienceDirect, ResearchGate, which is accessed in Google Scholar. The keywords of article search were using mobile phone and CPR. The initial stage of searching for information with the online database accessed at lib.ui.ac.id appeared 62 articles that brought them to the database. Furthermore, a search was carried out on Google Scholar which displayed 4.220 articles. From the search results, nine articles were found that matched the inclusion and exclusion criteria. Then a selection was made according to the inclusion criteria, articles from 2020 due to the latest 2020 AHA references. Full text and free forms are available, articles related to mobile phones and CPR. Exclusion criteria, articles that appear only abstract, the year before AHA 2020 and the suitability of the content is different from keyword searches. Results: Based on nine literature that requirements according to inclusion and exclusion criteria, the use of mobile phones could show a positive effect by activating a cellphone-based warning system that could detect cardiac arrest victims out of hospital, provided guidance the procedure at the right time, and assisted CPR outcomes with return of spontaneous circulation. Mobile phone applications can assist initiated-CPR immediately, provide guidance of procedures, and leads to better outcomes. In Indonesia there is no mobile phone application for CPR assistance, taking into account the increasing number of cardiac arrests and respiratory arrests both outside the hospital and inside the hospital, this application is expected to be able to help victims in a timely manner, guide rescuers and return circulation. spontaneous